Evaluation of the SSW Alfa Website using Webqual 4.0 Modification and Importance Performance Analysis - Auditi Kurnia Wijayanti; Asif Faroqi; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
Advancements in information technology have encouraged governments to digitize public services to enhance accessibility, transparency, and efficiency. The Surabaya Single Window (SSW) Alfa website was developed to facilitate public administrative processes. However, recurring user complaints regarding registration failures, verification delays, and system instability suggest weaknesses in service delivery. This study evaluates the quality of the SSW Alfa website using a modified WebQual 4.0 framework—expanded with reliability, trust, and citizen support—combined with the Importance Performance Analysis (IPA) method. The model consists of six variables: usability, information quality, service interaction quality, reliability, trust, and citizen support. A quantitative approach was employed by distributing a questionnaire to 385 users who had accessed the platform at least twice. Each item was assessed using a five-point Likert scale for both performance and importance. Data were analyzed using SPSS 29 and Excel. The largest gaps were found in information quality and reliability, with conformity level of 80–81%. The results showed an average conformity level of 93%, with most indicators producing negative gap values, indicating that actual performance falls short of user expectations. The IPA mapping identified four priority indicators in Quadrant I—information accuracy, information completeness, system reliability, and performance consistency—as critical areas for immediate improvement. These findings highlight the need for technical and content-related enhancements to better align digital services with user needs. This study contributes to the evaluation of e-government platforms by extending the WebQual model and offering actionable insights for improving digital service quality in the public sector.